THE IMMEDIATE EFFECTS OF KINESIO TAPE ON ANKLE BALANCE AND FUNCTIONAL PERFORMANCE IN ATHLETES WITH ANKLE SPRAIN, 17 - 25 YEARS OLD - Changkheaw, Atcharaphan (Academic Journal of Thailand National Sports University, 2022)
Research aims to determine immediate effects of kinesio tape on the ankle balance and functional performance in athletes with ankle sprain. The subjects consisted of 32 athletes at the ages of 17 - 25 years old with ankle sprain in The Thailand National Sports University, Samut Sakhon Campus. Subjects were simply randomly assigned to the experimental group of 16 immediately kinesio tape and the control group of 16 subjects to sham taping. The group was tested for ankle balance using the star excursion balance test and functional performance by using the single hope test before and after the experiment. The results showed that the ankle balance and functional performance of the control group after placebo tape installation was not significantly different from the pre-test at the .05 level. For the experimental group after applying kinesio tape, it was found that the ankle balance and functional performance were significantly different from before the experiment at the .05 level. There was no statistically significant difference in pretest between the control group and the experimental group at the .05 level. After the experiment, it was found that the ankle balance and functional performance of the experimental group were significantly different from the control group at the .05 level. Summary of research results from Kinesio tape attachment can increase ankle stability and function in athletes with ankle injuries.